Vibro-acoustic analysis of functionally graded circular discs under thermal environment. (27th October 2008) - Kumar, Boorle Rajesh; Ganesan, N.; Sethuraman, Raju
A circular disc made up of Functionally Graded Material (FGM) with several cases of FGM index are modelled and their vibration response to a harmonic point load in a thermal environment with temperature dependant material properties was computed by using the Finite Element Method (FEM). A macro was developed by the corresponding author in ANSYS Parametric Design Language for modelling FGM using the available physics in ANSYS. The acoustic response of a FGM circular disc was computed by coupling the vibration data from the FEM to the Boundary Element Method (BEM) using LMS SYSNOISE.